Role of NAFLD on the Health Related QoL Response to Lifestyle in Patients With Metabolic Syndrome: The PREDIMED Plus Cohort - Martínez-Urbistondo, Diego; San-Cristóbal, Rodrigo; Villares, Paula; Martínez-González, Miguel Ángel; Babio, Nancy; Corella, Dolores; del Val, José Luis; Ordovás, José Ma; Alonso-Gómez, Ángel M.; Wärnberg, Julia; Vioque, Jesús; Romaguera, Dora; et al. (Frontiers in Endocrinology, 2022)
Objective To evaluate the effect of Non-alcoholic fatty liver disease (NAFLD) status in the impact of lifestyle over Health-related quality of life (HRQoL) in patients with metabolic syndrome (MetS). Methods Baseline and 1 year follow up data from the PREDIMED-plus cohort (men and women, 55-75 years old with overweight/obesity and MetS) were studied. Adherence to an energy-restricted Mediterranean Diet (er-MeDiet) and Physical Activity (PA) were assessed with a validated screeners. Hepatic steatosis index (HSI) was implemented to evaluate NAFLD while the SF-36 questionnaire provided HRQoL evaluation. Statistical analyses were performed to evaluate the influence of baseline NAFLD on HRQoL as affected by lifestyle during 1 year of follow up. Results Data from 5205 patients with mean age of 65 years and a 48 % of female participants. Adjusted linear multivariate mixed regression models showed that patients with lower probability of NAFLD (HSI < 36 points) were more responsive to er-MeDiet (β 0.64 vs β 0.05 per er-MeDiet adherence point, p< 0.01) and PA (β 0.05 vs β 0.01 per MET-h/week, p = 0.001) than those with high probability for NAFLD in terms Physical SF-36 summary in the 1 year follow up. 10 points of er-MeDiet adherence and 50 MET-h/week were thresholds for a beneficial effect of lifestyle on HRQoL physical domain in patients with lower probability of NAFLD. Conclusion The evaluation of NAFLD by the HSI index in patients with MetS might identify subjects with different prospective sensitivity to lifestyle changes in terms of physical HRQoL (http://www.isrctn.com/ISRCTN89898870).